2011
DOI: 10.1177/0363546510390482
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Coracoclavicular Reconstructive Techniques

Abstract: Anatomic reconstruction of the coracoclavicular ligaments with allograft may provide a stronger biological solution for acromioclavicular joint dislocations. This reconstruction may minimize recurrent subluxation and pain and permit earlier rehabilitation when compared with current techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 26 publications
1
71
0
1
Order By: Relevance
“…10,11 Anatomic reconstructions of the CC ligaments using free tendon grafts have shown greater stability and load to failure than nonanatomic ligamentoplasty procedures such as the traditional Weaver-Dunn procedure and nonanatomic allograft, anatomic suture, and GraftRope techniques (Arthrex, Naples, FL). 7 They also more closely reproduce the function of the native CC ligaments. In a recent systematic review, Beitzel et al 12 found a lack of evidence in the literature to support a single technique as the "gold standard" for CC reconstruction.…”
Section: Coracoid Cerclage CC Reconstructionmentioning
confidence: 79%
See 1 more Smart Citation
“…10,11 Anatomic reconstructions of the CC ligaments using free tendon grafts have shown greater stability and load to failure than nonanatomic ligamentoplasty procedures such as the traditional Weaver-Dunn procedure and nonanatomic allograft, anatomic suture, and GraftRope techniques (Arthrex, Naples, FL). 7 They also more closely reproduce the function of the native CC ligaments. In a recent systematic review, Beitzel et al 12 found a lack of evidence in the literature to support a single technique as the "gold standard" for CC reconstruction.…”
Section: Coracoid Cerclage CC Reconstructionmentioning
confidence: 79%
“…In delayed and late reconstructions, multiple studies have shown that anatomic reconstruction using a tendon graft is superior in stability, load to failure, and reproduction of the native CC ligaments' function. [5][6][7] Anatomic reconstruction using tendon graft has been described by use of open and arthroscopic techniques. In the open approach, adequate access to the coracoid process for graft fixation requires deltoid detachment from the clavicle, as well as extensive soft-tissue dissection, and places the neurovascular structures at risk because of suboptimal visibility during graft transfer around the coracoid.…”
mentioning
confidence: 99%
“…This suspensory fixation device makes a hole in the coracoid process for transosseous fixation, which may avoid potential neurovascular injury that can be caused by approaching the base of the coracoid process to position the fixation material in the coracoid sling techniques, 8,9,14 Additionally, 4 strands of superior strength braided double polyethylene thread of the adjustableeloop-length suspensory fixation device provided stronger fixation in the CC interval compared with suture anchor fixation, which is loaded with weaker sutures. 15 Satisfactory clinical outcomes have already been reported regarding treatment of AC joint dislocation using the adjustableeloop-length suspensory fixation device. 7-10 Wellmann et al 8 fixed the CC interval in 15 patients using a flip button/polydioxanone system, which has a structure that is similar to the TightRope, and obtained excellent radiological results.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic reconstructions more closely reproduce the function of the native ligaments and show greater stability and load to failure. 10 However, the open technique as described by Carofino and Mazzoca 11 carries several potential risks including extensive soft tissue dissection, detachment of the deltoid from the clavicle for graft transfer around the coracoid base, and suboptimal visibility around the coracoid process during the graft transfer that may endanger the neurovascular structures.…”
Section: Discussionmentioning
confidence: 99%